Keabsahan Perjanjian Pengikatan Jual Beli dalam Putusan Pengadilan Negeri Denpasar Perkara Nomor 10/PDT.G/2019/PN.Dps - Alessandro Dimas Moersano; Riky Rustam (Fakultas Hukum Universitas Islam Indonesia, 2024)
This study aims to analyze the basic legal considerations used by the Judges at the Denpasar District Court to ratify the sale and purchase agreement in case number 10/Pdt.G/2019/PN.Dps. This study examines two legal issues: First, how is the validity of the sale and purchase agreement in the Denpasar District Court decision number 10/Pdt.G/2019/PN.Dps. Second, what is the accuracy of the legal considerations of the judges in the Denpasar District Court decision number 10/Pdt.G/2019/PN.Dps. The research method in this research is normative juridical which is based on literature studies, laws, books, journals, news and other supporting research. The results of this study can be concluded that: First, the notary was proven to have abused the authority granted by law during the process of making a sale and purchase agreement in case number 10/Pdt.G/2019/PN.Dps, causing the sale and purchase agreement to be degraded. Second, the legal considerations of the Judges examining case number 10/Pdt.G/2019/PN.Dps are incorrect because they state that the sale and purchase agreement is an authentic deed and states that the notary has carried out his duties according to applicable law. The researcher’s suggestion is that the judges should have been more careful in examining the evidence and ensuring the skills and competence of a notary as a person authorized to make authentic deeds.